Alcohol and substance use frequency in the female inmates of an İstanbul prison before the conviction - Akcan, Ayhan; Bıkım, Erdal; Akcan, Z Funda Engin; Samancı, Y Armağan; Balcıoğlu, İbrahim (Journal of Dependence, 2000)
The relationship between substance abuse and crime is an important issue which needs to be investigated for both social, economical and medical problems it causes. Ike prevention is to he established. The research on this topic has not recevied much attention in Turkey. Although these are a number of studies in developed countries The aim of the study is to state the importance of the issue. 39 02 of the subjects is this study have used alcohol and/or subtance at any time in their life span. Of the subjects, 18.29 % were under the influence of the alcohol and/or subtance. Ihe alcohol and/or subtance abuse is related to crime. Such relationship can imteract with gender, age, education, family structure and marital status. Those can be risk factors forboth the abuse and the crime.Prison healtcare is differant form the healthcare elsewhere Detoxification and withdrawal problems are of those prison healthcare problems. Turkey needs more studies on crime and alcohol-substance abuse. Ihe rehabilitation programs have to be set up in prison conditions.